2016
DOI: 10.1016/j.cjca.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heart Failure Biomarkers Predict Improvement of Mitral Regurgitation in Patients Receiving Cardiac Resynchronization Therapy—The BIOCRT Study

Abstract: Background Cardiac resynchronization therapy (CRT) improves mitral regurgitation (MR) in a subset of patients. We hypothesized that biomarkers (amino-terminal pro-B type natriuretic peptide [NT-proBNP], high-sensitivity troponin [hsTnI], galectin-3 [gal-3] and soluble ST-2 [sST2]) may predict MR response post-CRT. Methods We measured levels of biomarkers during CRT implantation in 132 patients with subsequent 2 years follow-up. MR was graded as no-trace, mild, moderate or severe at baseline and 6 months. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…LV reverse remodeling following TAVR does not occur equally in every patients, in particular in those with associated coronary artery disease. Future studies integrating myocardial imaging (viability) or biomarkers could help to better predict MR evolution after TAVR. In this era of percutaneous interventions advances, prediction of MR evolution after TAVR should be performed together with the evaluation of eligibility for eventual percutaneous (or surgical) mitral valve repair.…”
Section: Discussionmentioning
confidence: 99%
“…LV reverse remodeling following TAVR does not occur equally in every patients, in particular in those with associated coronary artery disease. Future studies integrating myocardial imaging (viability) or biomarkers could help to better predict MR evolution after TAVR. In this era of percutaneous interventions advances, prediction of MR evolution after TAVR should be performed together with the evaluation of eligibility for eventual percutaneous (or surgical) mitral valve repair.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial, the predictive value of Gal-3 and ST2 for MR reduction after cardiac resynchronization therapy implantation in HF patients were analyzed. 30 In the study of Beaudoin et al, elevated Gal-3 levels, indicating adverse cardiac remodeling, were associated with a lack of response to cardiac resynchronization therapy-related MR reduction, confirming the assumption that increased myocardial substrate and fibrosis at the cellular/molecular level may predict MR reduction after device therapy. 30 However, further validation in randomized trials that build on the results of the present study might make the procedure more reliable, and specific biomarker assessment might help to identify those patients who will benefit the most from PMVR using the MitraClip system.…”
Section: Discussionmentioning
confidence: 85%
“…In particular, the stability of Gal‐3 and ST2 is consistent, also with respect to differences in loading conditions, and is less affected by volume status; the fact that the predictive value of the fibrotic biomarkers ST2 and Gal‐3 was also more pronounced than BNP under these conditions confirms the diagnostic sensitivity of the fibrotic biomarkers examined in this study. In a recent trial, the predictive value of Gal‐3 and ST2 for MR reduction after cardiac resynchronization therapy implantation in HF patients were analyzed . In the study of Beaudoin et al, elevated Gal‐3 levels, indicating adverse cardiac remodeling, were associated with a lack of response to cardiac resynchronization therapy‐related MR reduction, confirming the assumption that increased myocardial substrate and fibrosis at the cellular/molecular level may predict MR reduction after device therapy .…”
Section: Discussionmentioning
confidence: 93%
“…A study conducted in Turkey to evaluate 54 patients who underwent CRT found that improved diastolic function was closely correlated with the decrease in BNP levels (from 270.5 pg/mL to 47.2 pg/mL, p<0.05) and BNP levels remained unchanged in patients without any improvement (from 646 pg/mL to 387.7 pg/mL, p=NS) (166). The study also showed that NT-proBNP levels were correlated with the improvement in mitral regurgitation (167); pro-atrial natriuretic peptides could also determine prognosis (168); natriuretic peptides gave information about prognosis in patients with mild heart failure (169); and natriuretic peptide levels were also associated with the improvement in right ventricular functions (170).…”
Section: Efficacy Of Natriuretic Peptide Levels In Assessing Responsementioning
confidence: 81%